Pesticides have negative effects on non-target organisms - Wan, Nian-Feng; Fu, Liwan; Dainese, Matteo; Kiær, Lars Pødenphant; Hu, Yue-Qing; Xin, Fengfei; Goulson, Dave; Woodcock, Ben A.; Vanbergen, Adam J.; Spurgeon, David J.; Shen, Siyuan; Scherber, Christoph (Nature communications, 2025)
Pesticides affect a diverse range of non-target species and may be linked to global biodiversity loss. The magnitude of this hazard remains only partially understood. We present a synthesis of pesticide (insecticide, herbicide and fungicide) impacts on multiple non-target organisms across trophic levels based on 20,212 effect sizes from 1,705 studies. For non-target plants, animals (invertebrate and vertebrates) and microorganisms (bacteria and fungi), we show negative responses of the growth, reproduction, behaviour and other physiological biomarkers within terrestrial and aquatic systems. Pesticides formulated for specific taxa negatively affected non-target groups, e.g. insecticidal neonicotinoids affecting amphibians. Negative effects were more pronounced in temperate than tropical regions but were consistent between aquatic and terrestrial environments, even after correcting for field-realistic terrestrial and environmentally relevant exposure scenarios. Our results question the sustainability of current pesticide use and support the need for enhanced risk assessments to reduce risks to biodiversity and ecosystems. Pesticides affect a diverse range of non-target species and the magnitude of this hazard remains only partially understood. Wan et al. found that insecticides, fungicides and herbicides have negative effects on non-target plants, animals and microorganisms within terrestrial and aquatic systems.